2009
DOI: 10.1016/j.atmosenv.2009.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric nitrogen deposition in south-east Scotland: Quantification of the organic nitrogen fraction in wet, dry and bulk deposition

Abstract: Water soluble organic nitrogen (WSON) compounds are ubiquitous in precipitation and in the planetary boundary layer, and therefore are a potential source of bioavailable reactive nitrogen. This paper examines weekly rain data over a period of 22 months from June 2005 to March 2007 collected in 2 types of rain collector (bulk deposition and "dry+wet" deposition) located in a semi-rural area 15 km southwest of Edinburgh, UK (N 55°51′44″, W 3°12′19″). Bulk deposition collectors are denoted in this paper as "stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The amount of organic N as a proportion of total N (inorganic + organic N) N deposition has been found to be about a third in mostly rural locations across 160 studies worldwide and 58 studies in North America (29% and 35%, respectively; Cornell, ). A similar proportion of organic N in total deposition has also been found in urban areas in studies around the world (Araujo et al, ; Chen et al, ; de Souza et al, ; González‐Benitez et al, ; He et al, ; Izquieta‐Rojano et al, ; Li et al, ; Matsumoto et al, ). There have been a handful of studies in the U.S. measuring organic N deposition in small towns in Connecticut and North Carolina, in winter precipitation in Salt Lake City, Utah and in Miami, Florida; four of these studies either do not report organic N deposition rates or do not report organic rates in the urban sites individually, and the others report the percentage of organic N in total N as below 20% (Brezonik et al, ; Hall et al, ; Keene et al, ; Luo et al, ; Nadim et al, ; Zamora et al, ).…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…The amount of organic N as a proportion of total N (inorganic + organic N) N deposition has been found to be about a third in mostly rural locations across 160 studies worldwide and 58 studies in North America (29% and 35%, respectively; Cornell, ). A similar proportion of organic N in total deposition has also been found in urban areas in studies around the world (Araujo et al, ; Chen et al, ; de Souza et al, ; González‐Benitez et al, ; He et al, ; Izquieta‐Rojano et al, ; Li et al, ; Matsumoto et al, ). There have been a handful of studies in the U.S. measuring organic N deposition in small towns in Connecticut and North Carolina, in winter precipitation in Salt Lake City, Utah and in Miami, Florida; four of these studies either do not report organic N deposition rates or do not report organic rates in the urban sites individually, and the others report the percentage of organic N in total N as below 20% (Brezonik et al, ; Hall et al, ; Keene et al, ; Luo et al, ; Nadim et al, ; Zamora et al, ).…”
Section: Introductionsupporting
confidence: 63%
“…Studies dating back over 100 years have shown organic N to be a substantial component of N deposited in rainwater (Miller, ), and others have shown dry deposition to be an important source of organic N (González‐Benitez et al, ; Matsumoto et al, ). Organic N includes a variety of molecules (e.g., urea, amines, and peptides) found in aqueous, particulate, and gaseous phases with a range of solubility and reactivity (Cape et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Aboveground standing biomass and net annual primary productivity (ANPP) were determined between April and October 2009 according to Vile et al [2006]. We also estimated N deposition at each of the sites from NEGTAP (Transboundary air pollution: Acidification, eutrophication and ground‐level ozone in the UK, 2001, http://www.freshwaters.org.uk/resources/documents/negtap_2001_final_report.pdf, accessed 04/03/11), with a 23% increase to account for organic N deposition [ González Benítez et al , 2009]. Details are provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The average contribution of ON to total nitrogen deposition to coastal water is 30%–40% [ Duce , 1998]. The impact of ON on the marine ecosystem depends on the sources, composition and abundance, however, not much is known [ Cornell et al , 2003; Nakamura et al , 2006; González Benítez et al , 2009].…”
Section: Introductionmentioning
confidence: 99%